Variation in coronary angiography rates in Australia: correlations with socio‐demographic, health service and disease burden indices. Issue 3 (1st August 2016) - Chew, Derek P; MacIsaac, Andrew I; Lefkovits, Jeffrey; Harper, Richard W; Slawomirski, Luke; Braddock, David; Horsfall, Matthew J; Buchan, Heather A; Ellis, Chris John; Brieger, David B; Briffa, Tom G
Abstract: Background: Variation in the provision of coronary angiography is associated with health care inefficiency and inequity. We explored geographic, socio‐economic, health service and disease indicators associated with variation in angiography rates across Australia. Methods: Australian census and National Health Survey data were used to determine socio‐economic, health workforce and service indicators. Hospital separations and coronary deaths during 2011 were identified in the National Hospital Morbidity and Mortality databases. All 61 Medicare Locals responsible for primary care were included, and age‐ and sex‐standardised rates of acute coronary syndrome (ACS) incidence, coronary angiography, revascularisation and mortality were tested for correlations, and adjusted by Bayesian regression. Results: There were 3.7‐fold and 2.3‐fold differences between individual Medicare Locals in the lowest and highest ACS and coronary artery disease mortality rates respectively, whereas angiography rates varied 5.3‐fold. ACS and death rates within Medicare Locals were correlated (partial correlation coefficient [CC], 0.52; P < 0.001). There was modest correlation between ACS and angiography rates (CC, 0.31; P = 0.018). The proportion of patients undergoing angiography who proceeded to revascularisation was inversely correlated with the total angiogram rate (CC, −0.71; P < 0.001). Socio‐economic disadvantage and remoteness were correlated with disease burden, ACS incidence and mortality, but not with angiography rate. In the adjusted analysis, the strongest association with local angiography rates was with admissions to private hospitals (71 additional angiograms [95% CI, 47–93] for every 1000 admissions). Conclusion: Variation in rates of coronary angiography, not related to clinical need, occurs across Australia. A greater focus on clinical care standards and better distribution of health services will be required if these variations are to be attenuated.